A BDI-based Multi-Agent System to Smart Parking Environment with Blockchain Technology - Oliveira, Gabriel L. M.; Alves, Gleifer Vaz; Lazarin, Nilson M. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
This paper presents the development of a BDI (Belief-Desire-Intention) multi-agent system integrated with blockchain technology for decentralized digital asset negotiation in a Smart Parking environment. Using the Velluscinum middleware, the system enables the use of NFT to represent parking spots. Tests demonstrated its feasibility and functionality, though limitations such as partial centralization and network dependency were noted. The work contributes to the integration of BDI agents and blockchain in Smart City contexts, with future improvements focused on decentralization and broader integration.